Edukasi Body Image, Stres, dan Status Gizi untuk Meningkatkan Kesehatan Remaja di SMPN 14 Pauh Padang - Fhadilla Amelia; Muhammad Hairil; Muhammad Tsaqif; Adisti Qamahadlina Larasati; Idral Purnakarya (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
Adolescents represent a population highly vulnerable to psychological and nutritional challenges. Global reports indicated that more adolescents experience mental health problems and national surveys showing rising concerns related to stress, body image, and unhealthy dietary habits. Academic pressure, peer dynamics, and widespread exposure to idealized body standards on social media further contribute to negative body image, increased stress levels, and poor eating behaviors. This community service program aimed to enhance students’ knowledge and awareness regarding body image, stress, and nutritional status through a structured school-based educational intervention. The activity was conducted at SMPN 14 Pauh, Padang City, involving 53 students. A pre–post intervention design was implemented, utilizing interactive presentations, participatory discussions, and brief ice-breaking activities, followed by pre-test and post-test assessments to measure changes in knowledge. A satisfaction survey was also administered to evaluate students’ perceptions of the session. The results demonstrated a significant increase in students’ knowledge scores after the educational session (p<0.001), with the highest improvement in questions related to body image and nutritional status. More than 90% of students expressed satisfaction with the materials, delivery methods, and the program’s relevance to their daily lives. These findings indicate that a short, targeted school-based intervention can effectively improve adolescents’ literacy in nutrition and mental well-being. Strengthening continuous programs through school health units and curricular integration is recommended to ensure sustained benefits and long-term impact on adolescent health.